Compact Oxford English dictionary of current English - Soanes, Catherine; Hawker, Sara. (Oxford ; New York : Oxford University Press, 2008)
"This revised third edition finds words quickly with easy-to-use design; can get you extra help with thousands of real examples plus usage and grammar notes; and improves your writing with practical advice in the Effective English section. It contains 150,000 words, phrases and definitions."--BOOK JACKET.
Machine derived contents note: Contents -- Preface iv -- Guide to the use of the dictionary v -- Abbreviations used in the dictionary x -- Compact Oxford English Dictionary 1 -- Effective English central section -- Note on trademarks and proprietary status -- This dictionary includes some words which have, or are asserted to have, proprietary -- status as trademarks or otherwise. Their inclusion does not imply that they have acquired -- for legal purposes a non-proprietary or general significance, nor any other judgement -- concerning their legal status. In cases where the editorial staff have some evidence that -- a word has proprietary status this is indicated in the entry for that word by the label -- trademark, but no judgement concerning the legal status of such words is made or implied -- thereby.
Previous ed.: 2005.
Includes index.
Keywords: English language -- Dictionaries